The Roles of Primary Emotional Systems and Need Satisfaction in Problematic Internet and Smartphone Use: A Network Perspective - Rozgonjuk, Dmitri; Davis, Kenneth L.; Montag, Christian (Frontiers in Psychology, 2021)
Problematic Internet and smartphone use (PIU and PSU, respectively) have received significant attention over the past years. In the current work, we studied the associations between PIU and PSU, primary emotional systems, and need satisfaction. The effective sample comprised 399 people who responded to scales measuring these variables. Bivariate correlation analysis showed that both PSU and PIU were associated with negative primary emotion traits (FEAR, ANGER, SADNESS) as well as lower scores on most of the need satisfaction factors. Network analysis showed that while PIU and PSU have a strong association with each other, in general, there were not many associations between PSU, PIU, and other variables in the network. The associations being present were weak. Higher PSU was positively associated with higher FEAR, ANGER, PLAY primary emotional systems, as well as with lower physiological, esteem, safety and security, and self-actualization needs satisfaction. Higher PIU, on the other hand, was associated with lower physiological and esteem need satisfaction. Addressing those unmet needs may be helpful in reducing problematic technology use, but further research testing this would be necessary.